Peran Food Vlogger Tasyi Athasyia dalam Mempengaruhi Keputusan Konsumen pada Pembelian Produk Makanan - Dini Safitri; Ivanna Rusli; Regina Regina; Syabilla Dwi Pahlovi (Jurnal Nomosleca, 2023)
The most popular content is about food, thus opening up a livelihood as a food vlogger. This research uses a qualitative approach, with exploratory research methods. The data confirmation technique uses the concept of source triangulation, namely by interviewing several different sources. Tasyi Athasyia's role as an influencer often provides personal views and experiences in consuming certain foods which serve as a source of information for consumers in choosing suitable food products. Tasyi Athasyia's influence as a food vlogger on purchasing food products can also be influenced by other factors such as the target market or certain market segments that are Tasyi Athasyia's audience. A successful influencer marketing campaign can also increase consumer trust in a brand or product, strengthen customer loyalty, and increase productsales. This study also explores the success of influencer marketing campaigns, such as those carried out by Tasyi, in increasing consumer trust in a brand or product.